Implementation of Digital Marketing in Increasing Awareness and Sales in The Beauty Industry Anty Shop 28 - Tuti Supatminingsih (International Journal of Education, Vocational and Social Science, 2023)
Cosmetic products that are currently getting good attention from the wider community who want to get beautiful skin as a whole are beauty products. Beauty products are ingredients used on external parts of the body such as the face, skin, hair and lips with the aim of cleaning, maintaining health, providing a fragrant aroma, and increasing a person's self-confidence. The aim of this research is to determine the influence of digital marketing on brand awareness of beauty products among the public. The analytical method used in this research is a qualitative approach. This approach collects data in the form of sentences or stories, with the aim of understanding various aspects such as behavior, perceptions, motivations and actions that occur in the field during research. The results are presented in easy-to-understand words in a scientific context, using the scientific method. This research focuses on understanding individual experiences in dealing with certain situations and can provide in-depth and complex insights about digital marketing in building awareness. The results of the analysis show that Anthy Shop's way of improving its digital marketing strategy related to the beauty products it sells is by testing new products that come into the store on average and then trying to understand their benefits or, at least, doing research about these products. Then use this knowledge to deliver products to customers or provide guidance to them. However, the shop owner realized that this method was not very effective due to the different skin types. Therefore, shop owners focus more on research than personal experience.